A thermodynamic constitutive model for shape memory polymers based on phase transition. (14th March 2022) - Xue, Yiheng; Lei, Jincheng; Liu, Zishun
Abstract: Shape memory polymers (SMPs) are a type of soft smart materials that can recover from the pre-deformed shape to the original shape under different external stimuli. Existing constitutive models fail to describe SME of SMPs under large and complex deformation. Based on thermodynamics and phase transition, we develop a constitutive model related to the deformation gradient and temperature for thermal-induced SMPs. A phenomenological expression of the stored deformation is introduced into the free-energy function to describe SME of SMPs. To verify the proposed model, we first compare our model with the literature experiments. Good consistency between our model and experimental results can be found out. We further carry out the experiments for a 3D printing SMP to investigate the availability of the model. The results demonstrate that the proposed model is effective to describe SME of SMPs under finite deformation. The proposed model can provide insights on describing SME of SMPs. Graphical abstract: Image 1 Highlights: Build a thermodynamic model for thermo-induced SMP in finite deformation framework. Introduce a phenomenological expression of the stored deformation gradient. Compare the model with three sets of experiments under different loading modes. Investigate the SME of a thin plate under biaxial loading using the proposed model.